Emergency Imaging in Pregnancy and Lactation. Issue 3 (August 2020) - Mathur, Shobhit; Pillenahalli Maheshwarappa, Ravishankar; Fouladirad, Saman; Metwally, Omar; Mukherjee, Pratik; Lin, Amy Wei; Bharatha, Aditya; Nicolaou, Savvas; Ditkofsky, Noah G.
The use of diagnostic imaging studies in the emergency setting has increased dramatically over the past couple of decades. The emergency imaging of pregnant and lactating patients poses unique challenges and calls upon the crucial role of radiologists as consultants to the referring physician to guide appropriate use of imaging tests, minimize risk, ensure timely management, and occasionally alleviate unwarranted trepidation. A clear understanding of the risks and benefits involved with various imaging tests in this patient population is vital to achieve this. This review discusses the different safety and appropriateness issues that could arise with the use of ionizing radiation, iodinated-, and gadolinium-based contrast media and radiopharmaceuticals in pregnant and lactating patients. Special considerations such as trauma imaging, safety concerns with magnetic resonance imaging and ultrasound, management of claustrophobia, contrast extravasation, and allergic reactions are also reviewed. The consent process for these examinations has also been described.